2018
DOI: 10.1038/s42004-018-0044-9
|View full text |Cite
|
Sign up to set email alerts
|

Trace mono-atomically dispersed rhodium on zeolite-supported cobalt catalyst for the efficient methane oxidation

Abstract: The partial oxidation of methane is a promising method for the efficient production of syngas. To implement this process using common stainless steel reactors, an inexpensive catalyst that functions at 650°C or below is necessary. However, base metal catalysts typically require much higher temperatures, and they are deactivated by re-oxidation and coke formation. Here we report that modification of a zeolite-supported 3 wt% cobalt catalyst with a trace amount of mono-atomically dispersed rhodium (0.005 wt%) dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…[69] In addition to 5d transition metal based catalysts, XAS has been used to determine the structure of SACs containing 4d noble metals such as Ru, Rh, and Pd atomically dispersed onto zeolites and MOFs. [70][71][72] Sun et al [70] studied Rh-based SACs and used Rh K-edge EXAFS measurements to determine the structural information of single Rh atoms encapsulated within S-1 zeolites (Rh@S-1-H and Rh@S-1-C). As shown in Figure 7A, upon comparison with Rh 2 O 3 and Rh foil references, Rh@S-1-C showed two major peaks corresponding to RhO and RhRh shells.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…[69] In addition to 5d transition metal based catalysts, XAS has been used to determine the structure of SACs containing 4d noble metals such as Ru, Rh, and Pd atomically dispersed onto zeolites and MOFs. [70][71][72] Sun et al [70] studied Rh-based SACs and used Rh K-edge EXAFS measurements to determine the structural information of single Rh atoms encapsulated within S-1 zeolites (Rh@S-1-H and Rh@S-1-C). As shown in Figure 7A, upon comparison with Rh 2 O 3 and Rh foil references, Rh@S-1-C showed two major peaks corresponding to RhO and RhRh shells.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Recently, various catalysts with precious and/or nonprecious metals for selective oxidation of CH 4 to CO and H 2 productions have been proposed [12][13][14][15][16][17][18][19][20][21] . In previous work, Kobayashi et al have reported a high performance using Rh/zeolite catalyst 18 ; Rh subnano clusters are formed on the MOR-type zeolite and this Rh/ MOR catalyst gave 84% CH 4 conversion and 91% selectivity for CO with H 2 /CO ratio of 2.0 at 873 K 18 .…”
mentioning
confidence: 99%
“…Kobayashi et al reported that mono-atomically dispersed Rh atoms on Co atoms played supportive roles that maintained an active Co 0 state for efficient methane oxidation. 15 (iv) Electronic interactions between isolated atoms and the surrounding atoms induce high activity. Sykes et al reported the selective hydrogenation of butadiene to butene over an isolated Ptatom-containing Pt−Cu alloy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Alloy catalysts are well known to exhibit unique catalytic behavior that is different from that of their monometallic counterparts, as a result of the “ligand effect” and the “ensemble effect”; however, the reaction mechanisms of alloy catalysts have not been fully elucidated yet. In particular, isolated atoms surrounded by the atoms of another element in the alloy, which are referred to as “single atom alloys (SAAs)”, have received significant attention. Although incipient reports of single-crystal SAA substrates have appeared in the surface science field, more practical nanoparticle catalysts have been reported in recent years. The electronic interactions and geometric positional relationships between single element “guest” atoms and the surrounding atoms of the “host” element are expected to induce unique catalytic behavior for the following four reasons. (i) Isolated atoms are active sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation